Pemikiran Pendidikan Islam Abdurrahman Mas’ud - Muhammad Rusdi Rasyid (Al-Riwayah : Jurnal Kependidikan, 2018)
This paper will examine the thoughts of Abdurrahman Mas'ud on Nondikotomik Educational Format (Humanism Religious as Paradigm of Islamic Education). Mas'ud argues, there is no separation between religious science and general science. Mas'ud seems to want to compromise the general assumption between Western education which is more concerned with the knowledge aspect with Eastern education emphasizing more on the Religious aspect. The educational goal according to Abdurrahman Mas'ud is the connection between man and his God (Hablum Minallah) and between man and man (Hablum Minannas). Ultimately, education aims to enable students to become human beings, which is perfect in the eyes of human civilization and perfect in the standard of religion. Furthermore, Mas'ud is in line with the concept of religious humanism that is applied in Islamic education by emphasizing on the aspects of teachers, aspects of methods, aspects of pupils, material aspects, and evaluation aspects